Minority language learning in Kven through conversation - Niiranen, Leena (Acta Borealia, 2021)
Language learners of Kven participated in informal learning settings using the Master Apprentice method, a method often used in language revitalization. The use of this method is studied in the light of sociocultural theory of language learning, which focuses on the relationship between collaborative learning and learner autonomy. The students of Kven improved their oral proficiency when using the language with the mentors in informal conversations. The informal learning setting increased learner autonomy among the participants because they exercised learner agency and used language learning strategies. Language learning takes place not only cognitively, but also emotionally. Anxiety can discourage learners from using language; self confidence influences the courage to speak. The MA method helped learners to master their negative feelings, and to lower anxiety. Positive feedback helped them take initiative for the use of the Kven language independently after first practising it with their mentor. However, beliefs about language learning seemed to guide the choice of learning activities. Practical activities, which are usually included in the use of the MA method, were not included, even though they would probably have influenced language learning in a positive way.